Dance Notation : a Historical Fact or a Necessity - Spalva, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
For centuries choreographers and dance theorists have been looking for ample signs to create a universal system for dance notation. Dance notation was created based on the need for a repeated staging of dances or for their preservation. However, unlike with music, no universal method of notation has been established allowing to capture dance techniques and compositions from different centuries in a single system. Nowadays, when video recording enables to capture each movement, dance or dance performance, the verbalgraphic style of dance notation can be perceived as dated an ineffective. However Latvia’s experience shows that contemporary dance teachers and choreographers have not yet abandoned the traditional notation system. The author of the article draws attention to dance notation research and analyses the need for it within dance education and in practice.